Utilizing YouTube as an Assistance for Improving Tertiary Students' Speaking Skill - Pusporini, Sekar Mayang; Rizal, Daviq (English Language in Focus (ELIF), 2024)
This research explores the use of YouTube as an English language learning tool to enhance speaking skills among university students. The aim is to determine the effectiveness of using YouTube as an English language learning tool in improving students' speaking skills. This research design used quantitative methods. The method for data collection was carried out by observation, namely questionnaires. The participants consisted of 90 students from various universities, with various semesters and different age groups. The findings indicate that a significant number of respondents use YouTube regularly for English language learning. This research contributes to understanding the role of YouTube in English language learning.